Numerical Calculations of Ion Scattering in Solids - Kwok, K. (My University, 1975)
The motion of energetic charged particles inside a crystalline solid is strongly dependent upon the orientation of the ion beam and target. This effect is commonly known as the "channeling" effect. In this report, the development of a computer code is presented which simulates the 3-D ion scatterings experienced by energetic particles moving in a crystalline solid. A Monte Carlo technique is incorporated in the code to calculate scattering angles, range distribution, backscattering distribution and angular distribution of incident ions. The Thomas-Fermi interatomic potential is used for binary collision process and the continuum potential is used for the potentials experienced by the channeled ions inside crystal lattices.
Keywords: ion scattering; numerical calculations; particles; crystalline solid; angular distribution; incident ions